Binding Potassium to Improve Treatment With Renin-Angiotensin-Aldosterone System Inhibitors: Results From Multiple One-Stage Pairwise and Network Meta-Analyses of Clinical Trials - Lizaraso-Soto, Frank; Gutiérrez-Abejón, Eduardo; Bustamante-Munguira, Juan; Martín-García, Débora; Chimeno, María Montserrat; Nava-Rebollo, Álvaro; Maurtua-Briseño-Meiggs, Álvaro; Fernández-Zoppino, Darío; Bustamante-Munguira, Elena; de Paz, Félix Jesús; Grande-Villoria, Jesús; Ochoa-Sangrador, Carlos; et al. (Frontiers in Medicine, 2021)
This manuscript presents findings from the first dichotomous data pooling analysis on clinical trials (CT) regarding the effectiveness of binding potassium. The results emanated from pairwise and network meta-analyses aiming evaluation of response to commercial potassium-binding polymers, i.e., to achieve and maintain normal serum potassium (n=1,722), and the association between this response and an optimal dosing of renin-angiotensin-aldosterone system inhibitors (RAASi) needing individuals affected by heart failure (HF) or resistant hypertension, who commonly consume other hyperkalemia-inducing drugs (HKID) (e.g., β-blockers, heparin, etc.), and frequently are affected by chronic kidney disease (CKD) (n=1044): According to the surface under the cumulative ranking area (SUCRA), sodium zirconium cyclosilicate (SZC) (SUCRA>0.78), patiromer (SUCRA>0.58) and sodium polystyrene sulfonate (SPS) (SUCRA<0.39) were different concerning their capacity to achieve normokalemia (serum potassium level (sK+) 3.5 to 5.0 mEq/L) or acceptable kalemia (sK+ ≤5.1 mEq/L) in individuals with hyperkalemia (sK+ >5.1 mEq/L), and, when normokalemia is achieved, patiromer 16.8 to 25.2 g/day (SUCRA=0.94) and patiromer 8.4 to 16.8 g/day (SUCRA=0.41) can allow to increase the dose of spironolactone up to 50 mg/day in subjects affected by heart failure (HF) or with resistant hypertension needing treatment with other RAASi. The potential of zirconium cyclosilicate should be explored further, as no data exists to assess properly its capacity to optimize dosing of RAASi, contrarily as it occurs with patiromer. Differences in the profile of patients affected by hyperkalemia should be considered to enlarge evidence in order to clarify a benefit of binding potassium for other groups of patients, for example, for patients taking RAASi but not having resistant hypertension, or considering only CKD or DM, etc.